Bibliographical research in the digital environment in forensic medicine (Saúde Ética & Justiça, 2004)
Now a days it is possible to make bibliographical research throught the Internet in some databases, that are gratuitously and also some with accesses regulated in the Institutions of education and research. This work brings information on the databases: Medline, Embase, ISI, Lilacs, SciELO. It informs periodic headings of forensic medicine that are indexed in the Medline, Embase and JCR/ISI.